UPAYA GURU DALAM MENINGKATKAN PRESTASI BELAJAR SEJARAH KEBUDAYAAN ISLAM KELAS IV-A DI MADRASAH IBTIDAIYAH BUSTANUL ULUM KOTA BATU - Yulia Kristanti; Khoirul Asfiyak; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractThis research was carried out in order to find out the improvement in students learning achievement in the subjects of history class IV-A Islamic culture of MI Bustanul Ulum Batu City. The problem faced is the number of students who ignore the teacher when learning takes place, this is due to students interest in learning about subjects of low islamic cultural history so that it impacts on students learning achievement which is not in accordance with the KKM (not yet reached 75) that has been set school. Data was obtained from the principal, class IV-A Islamic cultural history teacher, and IV-A grade students, amounting to 35 students. Approach used. In this study is a qualitative approach where data is obtained based on the results of interviews, observation, and documentation. The results of this study indicate that the teacher uses several efforts that have been designed and applied in learning so that the efforts made by the teacher can further optimize students learning achievement.  Keyword : achievement, students learning